Comparison of the Effects of Alcohol and Phenol Used for Celiac Neurolysis with Endoscopic Ultrasound in Patients with Pancreas Cancer: Retrospective Analysis - Birzat Emre Gölboyu; Uğur Özgürbüz (Genel Tıp Dergisi)
Objective: In this study we aimed to compare the efficacy of ethanol and phenol used in the EUS-guided celiac plexus neurolysis procedure on pain scores and complications. Material and Methods: Between January 2009 and June 2022, 28 patients who underwent celiac neurolysis underwent sedation via EUS (endoscopic ultrasonography) guidance in the endoscopy unit were included. We retrospectively analyzed the data of the EUS-guided celiac neurolysis procedures for pain management of patients with pancreatic cancer. Results: Patients in the alcohol group had lower pain scores. Conclusion: When alcohol and phenol-based neurolytic techniques were compared, better analgesic effect was obtained in the alcohol group.